Fabrication method of platinum-carbon catalyst for polymer electrolyte membrane fuel cell
Patent Information
- Application Number
- KR1020240177113
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2044-12-03
Smart Images

Figure 112024133633425-PAT00004_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing a platinum-carbon catalyst for a polymer electrolyte membrane fuel cell. Background Technology
[0002] Polymer Electrolyte Membrane Fuel Cells (PEMFCs) are power generation technologies that directly convert chemical energy into electrical energy through the electrochemical reaction of hydrogen and oxygen, and they are gaining attention as a future energy source due to their eco-friendly characteristics.
[0003] Catalysts, a key component of PEMFCs, play a role in lowering the activation energy during the oxidation and reduction of hydrogen and the reduction and oxidation of oxygen. Since the performance of these catalysts significantly impacts the overall performance and efficiency of the fuel cell, it is necessary to develop catalysts with high activity and durability.
[0004] Conventionally, PEMFC catalysts primarily used are precious metal catalysts such as platinum. While precious metal catalysts offer excellent performance, their utilization is limited by high costs and restricted production volumes. To address these issues, research and development on non-precious metal catalysts have been conducted, but it remains difficult to achieve performance comparable to that of precious metal catalysts. Consequently, researchers are continuing their efforts to develop methods to reduce the amount of precious metal catalysts used or increase loading efficiency in order to maximize the utilization of limited precious metal resources. Prior art literature
[0005] U.S. Patent Publication No. 9123976 The problem to be solved
[0006] The objective of the present invention is to provide a method for manufacturing a platinum-carbon catalyst that can exhibit superior electrochemical activity compared to commercial catalysts when applied to a polymer electrolyte membrane fuel cell. means of solving the problem
[0007] A method for manufacturing a platinum-carbon catalyst for a polymer electrolyte membrane fuel cell according to the present invention comprises: a first step of preparing a carbon black dispersion and a platinum precursor aqueous solution by mixing ethylene glycol and carbon black, respectively; a second step of preparing a reaction solution by adding the ethylene glycol and the platinum precursor aqueous solution to the carbon black dispersion; and a third step of adjusting the pH to greater than 3 and less than or equal to 8 by adding an inorganic base to the reaction solution.
[0008] In a method for manufacturing a platinum-carbon catalyst for a polymer electrolyte membrane fuel cell according to one embodiment of the present invention, the carbon black dispersion may be characterized by being prepared by mixing 500 to 900 ml of ethylene glycol per 1 g of carbon black.
[0009] In a method for manufacturing a platinum-carbon catalyst for a polymer electrolyte membrane fuel cell according to one embodiment of the present invention, the platinum precursor in the first step may be characterized by being added in an amount of 0.1 to 0.3 g relative to 1 g of carbon black, based on the platinum content contained within the platinum precursor.
[0010] In a method for manufacturing a platinum-carbon catalyst for a polymer electrolyte membrane fuel cell according to one embodiment of the present invention, the platinum precursor aqueous solution may be characterized by being prepared by mixing 50 to 300 ml of water and a platinum precursor per 1 g of carbon black.
[0011] In a method for manufacturing a platinum-carbon catalyst for a polymer electrolyte membrane fuel cell according to one embodiment of the present invention, the ethylene glycol mixed in the second step may be characterized as being 500 to 900 ml per 1 g of carbon black.
[0012] In a method for manufacturing a platinum-carbon catalyst for a polymer electrolyte membrane fuel cell according to one embodiment of the present invention, the second step may be characterized by adding water together with an aqueous solution of ethylene glycol and a platinum precursor to a carbon black dispersion, wherein 200 to 500 ml of water is added per 1 g of carbon black.
[0013] A method for manufacturing a platinum-carbon catalyst for a polymer electrolyte membrane fuel cell according to one embodiment of the present invention may further include a heating step of heating to 100 to 200 ℃ after the third step.
[0014] The present invention also provides a platinum-carbon catalyst for a polymer electrolyte membrane fuel cell manufactured by a manufacturing method according to one embodiment of the present invention.
[0015] A platinum-carbon catalyst for a polymer electrolyte membrane fuel cell according to one embodiment of the present invention may be characterized by having a platinum introduction amount of 0.5 at% or more based on the results of Energy-dispersive X-ray spectroscopy (EDS) analysis.
[0016] The platinum included in the platinum-carbon catalyst for a polymer electrolyte membrane fuel cell according to one embodiment of the present invention may be characterized by having an average particle size of 2 to 6 nm.
[0017] The present invention also provides a polymer electrolyte membrane fuel cell comprising an electrode having a coating layer formed thereon containing a platinum-carbon catalyst for a polymer electrolyte membrane fuel cell according to one embodiment of the present invention. Effects of the invention
[0018] The method for manufacturing a platinum-carbon catalyst for a polymer electrolyte membrane fuel cell according to the present invention comprises: a first step of preparing a carbon black dispersion and a platinum precursor aqueous solution by mixing ethylene glycol and carbon black, respectively; a second step of preparing a reaction solution by adding the ethylene glycol and the platinum precursor aqueous solution to the carbon black dispersion; and a third step of adjusting the pH to greater than 3 and less than or equal to 8 by adding an inorganic base to the reaction solution; wherein the catalyst prepared by this method exhibits superior electrochemical activity compared to commercial catalysts when applied to a polymer electrolyte membrane fuel cell. Brief explanation of the drawing
[0019] Figure 1 shows the results of analyzing the Pt / C catalyst and carbon black of the embodiments and comparative examples of the present invention by X-ray Diffraction (XRD). Figure 2 shows the results of analyzing the Pt / C catalyst prepared in an embodiment of the present invention using FE-SEM (Field Emission Scanning Electron Microscope) and EDS (Energy-dispersive X-ray spectroscopy) mapping. Figure 3 shows the results of measuring the zeta potential of carbon black. Figure 4 shows the results of performing CV (Cyclic Voltammetry) analysis using a Pt / C catalyst prepared in an embodiment of the present invention. Figure 5 illustrates the results of analyzing the electrochemical active area (ECSA) based on the CV analysis results performed in an embodiment of the present invention. Specific details for implementing the invention
[0020] The advantages and features of the embodiments of the present invention, and the methods for achieving them, will become clear by referring to the embodiments described below in detail together with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below but may be implemented in various different forms. These embodiments are provided merely to ensure that the disclosure of the present invention is complete and to fully inform those skilled in the art of the scope of the invention, and the present invention is defined only by the scope of the claims. Throughout the specification, the same reference numerals refer to the same components.
[0021] In describing the embodiments of the present invention, specific descriptions of known functions or configurations will be omitted if it is determined that such detailed descriptions could unnecessarily obscure the essence of the invention. Furthermore, the terms described below are defined in consideration of their functions in the embodiments of the present invention, and these definitions may vary depending on the intentions or practices of the user or operator. Therefore, such definitions should be based on the content throughout this specification.
[0022] A method for manufacturing a platinum-carbon catalyst for a polymer electrolyte membrane fuel cell according to the present invention comprises a first step of preparing a carbon black dispersion and a platinum precursor aqueous solution, respectively, by mixing ethylene glycol and carbon black;
[0023] A second step of preparing a reaction solution by adding an aqueous solution of ethylene glycol and a platinum precursor to the carbon black dispersion; and
[0024] A third step of adding an inorganic base to the above reaction solution to adjust the pH to greater than 3 and less than or equal to 8; is included.
[0025] The method for manufacturing a platinum-carbon catalyst for a polymer electrolyte membrane fuel cell according to the present invention has the advantage of being able to manufacture a platinum-carbon catalyst with excellent catalytic activity compared to commercial catalysts in a simple manner by including the first to third steps above.
[0026] Specifically, the method for manufacturing a platinum-carbon catalyst according to the present invention has the advantage of being able to produce a platinum-carbon catalyst with small and uniform particle size, excellent loading efficiency, and excellent catalytic activity by mixing ethylene glycol, carbon black, and a platinum precursor to first perform a reduction reaction of the platinum precursor, and then adding an inorganic base to adjust the pH.
[0027] In the first step, the carbon black dispersion can be prepared by mixing 500 to 900 ml, preferably 550 to 750 ml, of ethylene glycol per 1 g of carbon black. By mixing carbon black and ethylene glycol and performing dispersion before mixing with the platinum precursor, the carbon black is uniformly dispersed, which has the advantage of allowing platinum particles to be evenly introduced into the carbon black.
[0028] The platinum precursor included in the aqueous solution of the platinum precursor in the first step may include one or more selected from PtCl2, H2PtCl6·6H2O, [Pt(NH₃)₄]Cl₂, Pt(acac)₂, and [Pt(PMe₃)₄]. Based on the platinum content contained within the platinum precursor in the first step, 0.1 to 0.3 g of platinum, preferably 0.15 to 0.25 g, may be added per 1 g of carbon black. When a small amount of platinum is added, it is difficult for platinum to be sufficiently loaded into the carbon black, and when a large amount of platinum is added, although the increase in the loading amount is minimal, a problem may arise in which the proportion of platinum discarded after the reaction increases. The platinum precursor aqueous solution may use 50 to 300 ml of water, preferably 70 to 250 ml, per 1 g of carbon black, and in this invention, water may refer to deionized water, ultrapure water, etc. from which impurities have been removed.
[0029] The method for manufacturing a platinum-carbon catalyst according to the present invention includes a second step of preparing a reaction solution by adding an aqueous solution of ethylene glycol and a platinum precursor to the carbon black dispersion. In the second step, ethylene glycol and a platinum precursor are mixed to primarily produce nano-scale platinum particles. The amount of ethylene glycol added in the second step may be 500 to 900 ml, preferably 550 to 750 ml, per 1 g of carbon black. If a small amount of ethylene glycol is included, the reduction of platinum may not occur sufficiently or the reduction reaction may be slowed down. If a large amount of ethylene glycol is included, the rate or efficiency of the platinum reduction reaction may not increase further, while the catalyst production cost and waste disposal cost may increase.
[0030] In the second step, water can be additionally added in addition to the carbon black dispersion, ethylene glycol, and platinum precursor aqueous solution. By adding water to control the viscosity, a uniform reduction reaction can be promoted, which is an advantage. At this time, 200 to 500 ml, preferably 250 to 450 ml, of water can be added per 1 g of carbon black. If a small amount of water is added, it is difficult to achieve a uniform reduction reaction promotion effect, and if a large amount of water is added, a problem may arise that promotes the aggregation of the generated platinum nanoparticles.
[0031] The method for preparing a platinum-carbon catalyst according to the present invention includes a third step of adding an inorganic base to the reaction solution to adjust the pH to 5 to 8. At this time, the inorganic base may include one or more selected from sodium hydroxide, potassium hydroxide, lithium hydroxide, and ammonia, and preferably sodium hydroxide or potassium hydroxide may be used.
[0032] The third step may be a step of adjusting the pH of the reaction solution to greater than 3 and less than or equal to 8, preferably 5 to 8, more preferably 5.5 to 7.5, and most preferably 5.7 to 7. By satisfying this pH, the average size of platinum particles contained in the platinum-carbon catalyst produced may satisfy 2 to 6 nm, preferably 2.8 to 4 nm. In this range, the platinum-carbon catalyst is characterized by exhibiting significantly superior catalytic activity compared to commercial catalysts.
[0033] Specifically, the third step may include the process of adding an inorganic base alone or adding an aqueous solution of an inorganic base with a concentration of 0.1 to 1.5 M by weight%, and the inorganic base may be added by titrating until a target pH is reached. If the target pH is low, the platinum particle size becomes excessively large, which may lead to a decrease in durability and problems with platinum detachment from the carbon material; if the target pH is high, the platinum particle size becomes smaller, but there is a limitation in that it is difficult to exhibit sufficient catalytic activity.
[0034] A method for preparing a platinum-carbon catalyst according to one embodiment of the present invention may further include a heating step of heating the reaction solution after the third step. At this time, the heating may be a step of heating the reaction solution to 100 to 200 ℃, preferably 110 to 160 ℃, and through the heating step, the unreduced platinum is reduced and nano-scale platinum particles can be introduced into the carbon black.
[0035] A platinum-carbon catalyst can be finally prepared by washing the precipitate generated after heating with water, ethanol, etc., and drying it.
[0036] A platinum-carbon catalyst prepared by the method according to one embodiment of the present invention can satisfy a platinum introduction amount of 0.5 at% or more, preferably 0.6 to 1 at%, based on EDS (Energy-dispersive X-ray spectroscopy) analysis. By satisfying this range, excellent catalytic activity compared to commercially available catalysts can be secured, and specifically, an ECSA Loss of 15% or less, preferably 13% or less can be satisfied.
[0037] The present invention also includes a polymer electrolyte membrane fuel cell, wherein the polymer electrolyte membrane fuel cell according to the present invention may include an electrode having a coating layer formed thereon containing the platinum-carbon catalyst described above. The polymer electrolyte membrane fuel cell according to the present invention has the advantage of achieving high efficiency with high catalytic activity compared to the case where a commercially available catalyst is applied.
[0039] The present invention will be explained in detail below through examples and comparative examples. The following examples are intended only to aid in understanding the present invention, and the scope of the present invention is not limited by the following examples.
[0040] [Preparation Example]
[0041] 64 ml of ethylene glycol and 0.1 g of carbon black (Vulcan-XC72R) were added to a two-necked round-bottom flask, and after ultrasonic irradiation for 1 minute, the mixture was stirred at 750 rpm for 2 minutes to prepare a uniformly dispersed carbon black solution. Separately, a platinum precursor solution was prepared by dispersing a platinum precursor (H2PtCl6·6H2O) in 10 ml of deionized water. 36 ml of ultrapure water and 64 ml of ethylene glycol were added to the carbon black solution, and the platinum precursor solution was additionally added and mixed. During this mixing, the platinum precursor was reduced by the reducing properties of ethylene glycol, thereby forming nano-sized platinum particles. Subsequently, the pH of the reaction solution was adjusted by titrating and adding a 1 M aqueous sodium hydroxide solution, and the amount of sodium hydroxide solution added was controlled so that the pH reached 3, 6, 10, and 11, respectively, after the addition of the sodium hydroxide.
[0042] After the reaction, platinum particles were adsorbed onto the carbon surface by heat treatment at 140°C for 2 hours in a heating mantle, and the carbon black catalyst (Pt / C) was prepared by repeating washing and filtration using ethanol and distilled water, and drying at 60°C for 24 hours.
[0043] At this time, when preparing the platinum precursor solution, the amount of platinum precursor added was calculated and introduced so that the final Pt / C catalyst produced contains 20 wt% platinum.
[0045] Analysis of the manufactured catalyst
[0046] A commercial Pt / C catalyst containing 20 wt% platinum, a Pt / C catalyst prepared in the preparation example, and commercial carbon black were analyzed by X-ray Diffraction (XRD), and the results are shown in Figure 1.
[0047] Referring to Figure 1, the (002) peak of carbon was identified at 24.4°, and when comparing the commercial catalyst and the Pt / C catalyst prepared in the example, platinum peaks were found at 39.9° (111), 46.4° (200), 67.6° (220), and 81.6° (311). When comparing the existing commercial Pt / C catalyst and the prepared Pt / C catalyst, it can be seen that for the other catalysts, excluding the Pt / C prepared under pH 11 conditions, the intensity of the platinum peak is greater than that of the carbon peak.
[0048] When comparing the peaks of Pt / C prepared in each preparation example, it can be observed that the platinum peak becomes sharper as the pH decreases and becomes acidic, which can be attributed to the increased particle size of the introduced platinum nanoparticles. The particle size of platinum was analyzed using the Scherrer formula, and the average particle size of the analyzed platinum is shown in Table 1 below.
[0050] Sample types Commercial Pt / C Preparation Example pH 3 6 10 11 Particle size (nm) 1.91 10.54 3.33 2.56 1.64
[0051] Referring to Table 1, it can be seen that the particle size decreases as the pH increases, and that the particle size decreases rapidly between pH 3 and 6. When platinum particles are manufactured under conditions of pH 3, the average particle size exceeds 10 nm, which raises concerns about reduced durability and risks that the platinum particles may easily detach from the carbon black.
[0053] Microstructure and Dispersion Analysis
[0054] The Pt / C catalysts prepared in each preparation example were analyzed using Field Emission Scanning Electron Microscope (FE-SEM) and Energy-dispersive X-ray spectroscopy (EDS) mapping, and the results are shown in Fig. 2. Figs. 2a, b, and c show the results of observing the prepared Pt / C catalysts with FE-SEM at pH values of 3, 6, and 10, respectively, showing that platinum is supported on a carbon support of nano-sized particles. Figs. 2d, e, and f show the EDS mapping results of the platinum contained in the prepared platinum catalysts at pH values of 3, 6, and 10, respectively, showing that platinum is uniformly dispersed at all pH values.
[0055] Based on the EDS analysis results, the platinum content loaded on the surface of carbon black was analyzed, and the results are shown in Table 2 below. Referring to Table 2, it can be seen that as the amount of NaOH added increases and the pH rises, the platinum loading efficiency decreases, and based on the previous results, it can be confirmed that the platinum particle size decreases simultaneously. In addition, based on the EDS analysis results, the loading amount relative to the amount of platinum added was compared, and it was confirmed that the highest loading amount was observed when prepared under pH 3 conditions; however, this is due to the introduction of platinum with large particle sizes, and it was confirmed that the best loading efficiency in the average particle size range of 5 nm or less was achieved when prepared under pH 6 conditions.
[0057] Sample types Preparation Example pH 3 6 10 Platinum introduced (at%) 1.1 0.6 0.55 Loading efficiency (wt%) 13.5 8.6 7
[0058] Verification of zeta potential according to catalyst manufacturing conditions
[0059] Figure 3 illustrates the observed change in zeta potential according to pH change. Zeta potential measures the potential difference of the electric double layer formed around colloidal particles or other small particles. In the case of carbon black, the zeta potential drops to a negative value as pH increases, but becomes positive as pH decreases, whereas in the case of platinum, the zeta potential has a negative value. When the pH is low, the zeta potentials of carbon black and platinum particles have opposite charges, allowing platinum particles to be adsorbed well onto carbon black. However, when the pH decreases, it affects the concentration of glycolate ions, which can cause a problem where the size of platinum particles increases.
[0061] Evaluation of electrochemical properties
[0062] For the preparation examples at pH 6, 10, and 11 in which the average platinum particle size was measured to be 10 nm or less, cyclic voltammetry (CV) was used for analysis, and the results are shown in Figure 4. Specifically, a catalyst ink was prepared by mixing 4 mg of the catalyst prepared in each preparation example, 1.5 mL of isopropanol, 50 µL of Nafion resin, and 0.5 mL of distilled water, and then coated onto a working electrode and dried. In addition, Ag / AgCl was used as the reference electrode, a platinum electrode as the counter electrode, and a 0.1 M HClO4 solution as the electrolyte. The experiment was performed by injecting at a scanning rate of 20 mV / s at 0.8 to -0.2 V under a nitrogen atmosphere and repeating this process for up to 500 cycles. Figure 4 shows the measurement results for a commercial catalyst, b at pH 6, c at pH 10, and d at pH 12.
[0063] Furthermore, based on the CV measurement results, the electrochemical surface area (ECSA) was measured and shown in Figure 5, and the ECSA loss (%) was calculated and shown in Table 3 below.
[0065] Sample types Commercial Pt / C Preparation Example pH 6 10 11 ECSA Loss(%) 33.6 11.3 31.6 41.3
[0066] Referring to Figures 4 and 5 and Table 3, it can be seen that, except for the case where the catalyst prepared under pH 11 was applied, all exhibited superior catalytic activity compared to commercial Pt / C. In particular, when prepared under pH 6, the ECSA Loss was 15% or less, preferably 13% or less, which is significantly higher than the ECSA Loss of commercial Pt / C, which is approximately 33%.
Claims
Claim 1 A method for manufacturing a platinum-carbon catalyst for a platinum-loaded polymer electrolyte membrane fuel cell, comprising: a first step of preparing a carbon black dispersion and a platinum precursor aqueous solution by mixing ethylene glycol and carbon black, respectively; a second step of preparing a reaction solution by adding the ethylene glycol and the platinum precursor aqueous solution to the carbon black dispersion; and a third step of adjusting the pH to 5.5 to 7.5 in a single process by adding an inorganic base to the reaction solution, wherein the carbon black dispersion is prepared by mixing 500 to 900 ml of ethylene glycol per 1 g of carbon black, the platinum precursor satisfies 0.1 to 0.3 g relative to 1 g of carbon black based on the platinum content contained within the platinum precursor, and the platinum-carbon catalyst has a platinum introduction amount of 0.6 to 1 at% based on the results of EDS (Energy-dispersive X-ray spectroscopy) analysis. Claim 2 delete Claim 3 delete Claim 4 A method for manufacturing a platinum-carbon catalyst for a polymer electrolyte membrane fuel cell, characterized in that, in claim 1, the platinum precursor aqueous solution is prepared by mixing 50 to 300 ml of water and a platinum precursor per 1 g of carbon black. Claim 5 A method for manufacturing a platinum-carbon catalyst for a polymer electrolyte membrane fuel cell, characterized in that, in claim 1, the ethylene glycol mixed in the second step is 500 to 900 ml per 1 g of carbon black. Claim 6 A method for manufacturing a platinum-carbon catalyst for a polymer electrolyte membrane fuel cell, wherein, in claim 1, the second step further involves adding water to the carbon black dispersion along with an aqueous solution of ethylene glycol and a platinum precursor, wherein 200 to 500 ml of water is added per 1 g of carbon black. Claim 7 A method for manufacturing a platinum-carbon catalyst for a polymer electrolyte membrane fuel cell, characterized in that, in claim 1, it further includes a heating step of heating to 100 to 200 ℃ after the third step. Claim 8 A platinum-carbon catalyst for a polymer electrolyte membrane fuel cell manufactured by the manufacturing method selected from any one of claims 1 and 4 to 7. Claim 9 delete Claim 10 A platinum-carbon catalyst for a polymer electrolyte membrane fuel cell according to claim 8, characterized in that the platinum included in the platinum-carbon catalyst has an average particle size of 2 to 6 nm. Claim 11 A polymer electrolyte membrane fuel cell comprising an electrode having a coating layer formed thereon containing a platinum-carbon catalyst for a polymer electrolyte membrane fuel cell according to claim 8.
